Pan-European Sarcoma Trials:Moving Forward in a Climate of Increasing Economic and Regulatory Pressure. - Carrle, Dorothe; Dantonello, Tobias; Bielack, Stefan S. (Sarcoma, 2007)
Advances in sarcoma treatment are largely based on investigator-initiated, multicentric and interdisciplinary clinical trials. The EU's Good Clinical Practice Directive 2001/20/EC, effective since 2004, was meant to harmonize the conditions for clinical trials across Europe, but, instead, the challenge of initiating and running multinational, noncommercial clinical trials has become greater than ever. Institutions participating in existing noncommercial Pan-European studies are struggling to cope with increased administrative and financial burdens, and few new studies are initiated any more. The aim of a conference entitled ‘Pan-European Sarcoma Trials: Moving Forward in a Climate of Increasing Economic and Regulatory Pressure,’ held in Stuttgart, Germany, 30 November-2 December 2006 as part of the European Science Foundation's ECT-program, was not only to provide an overview of currently active and plannedmultinational studies on osteo-, Ewing's, and soft tissue sarcoma, but also to draw on areas of synergy between various established sarcoma groups in Europe to define plausible survival strategies for collaborative, interdisciplinary, patient-oriented research.